Implementasi Metode Pembelajaran Kepesantrenan pada Masa Pandemi di Pondok Pesantren Miftahussalam Banyumas - Ensi Sadita Anjar; A. Sulaeman (Proceedings Series on Social Sciences & Humanities, 2022)
Implementation of learning methods is the implementation of learning methods used by teachers in learning. The learning methods applied during the pandemic are usually different from before, therefore the purpose of this study is to find out how the Implementation of Islamic Boarding School Learning Methods during the Pandemic Period at the Miftahussalam Islamic Boarding School Banyumas. This study uses a qualitative research type, which is a research method used to examine the condition of natural objects, where the researcher is the key instrument. Data collection techniques are interviews, observations, and documentation. Data analysis used primary data from interviews and document data from the applicable Miftahussalam Islamic Boarding School Banyumas. Data analysis became a guide for research. Qualitative research, data analysis is more focused during the process in the field along with data collection. Meanwhile, from the technique of presenting the data, the research uses a descriptive pattern. This study shows that the implementation of Islamic boarding school learning during the pandemic was initially hampered but after collaborating with the Covid-19 task force in Banyumas, Islamic Boarding Schools were able to carry out Islamic Boarding School learning as usual even though many Islamic Boarding materials were not delivered to the students to the maximum. The implementation of the Islamic boarding school learning method runs as usual, namely the lecture method, memorization, dictation (writing in Arabic), questions and answers, and so on. The final result of this study is that the implementation of learning is carried out offline with the same method before the pandemic.